Neolithic long-distance exchanges in Southern Arabia: A supposed road for the 'Jade' axes. (October 2021) - Al Kindi, Mohammed; Charpentier, Vincent; Pia Maiorano, Maria; Musa, Maya; Pavan, Alexia; Heward, Alan; Vosges, Jérémie; Marchand, Grégor; Pickford, Martin
Abstract: This paper discusses the results of a new geo-archaeological study on the nephrite (jade) axes discovered in southern Oman (Dhofar Governorate). The research presents a first account of the geological composition and the morphological structure of such tools and it outlines a preliminary distribution network of jade axe-heads across Southern Arabia. After the discovery of the first analysed sample at Shaqat Jadailah SQJ-3, in the Rub' al-Khali Desert (Dhofar), four other archaeological axe-adze samples collected from southern Oman, were analysed using micro-Raman Spectroscopy and Energy Dispersive X-Ray Fluorescence (ED-XRF). We compared the analysed samples to other nephrite axes collected in the first pioneering exploration of Gertrude Caton-Thompson (Yemen) and Wilfred Thesiger (South Oman). These objects were then correlated with nephrite raw material from the basement exposures in Yemen. Available data show that the raw material originating in Yemen reached the Neolithic groups of Southern Rub' al-Khali and coastal Dhofar most likely during the 6th-5th millennium BC, following a similar path to the obsidian route. The colour, texture and composition, together with the presence of other classes of lithic artefacts such as the trihedral projectile points, indicate that during this period Southern Oman was fully integrated into long-distance exchange networks. The analysis of the collected samples show that they are made exclusively from nephrite, and not from other general "green stones". Considering the high hardness and toughness of the nephrite, this fact allows the hypothesis of a deliberate choice in the selection of raw material for its durability or prestige value.